Impulse Purchases, Gun Ownership and Homicides: Evidence from a Firearm Demand Shock - Christoph Koenig; David Schindler (Center for Economic Studies and ifo Institute (CESifo), 2019)
Do firearm purchase delay laws reduce aggregate homicide levels? Using quasi-experimental evidence from a 6-month countrywide gun demand shock starting in late 2012, we show that U.S. states with legislation preventing immediate handgun purchases experienced smaller increases in handgun sales. Our findings are hard to reconcile with entirely rational consumers, but suggest that gun buyers behave time-inconsistently. In a second step, we demonstrate that states with purchase delays also witnessed 2% lower homicide rates during the same period compared to states allowing instant handgun access. We report suggestive evidence that lower handgun sales primarily reduced impulsive assaults and domestic violence.
Keywords: K42; H76; H10; K14; 330; guns; murder; Sandy Hook; gun control; impulsiveness